FAKTOR YANG MEMPENGARUHI KARAKTERISTIK GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN NON KEUANGAN SUBSEKTOR MAKANAN DAN MINUMAN - Mike Kusuma Dewi; Meri Andani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to test factors that influence the characteristics of good corporate governance (GCG) against corporate social responsibility (CSR) disclosure in non-financial food and beverage subsectors in the IDX 2016-2020. Based on purposive sampling, the number of Food and Beverage Subsector companies used in the study sample was as many as 12 companies. Hypothesis testing uses regression panel data using the E Views 8.0 program. The results showed that the board of commissioners had a significant positive effect on CSR, Leverage had no effect on CSR and the size of the company had no effect on CSR